1989
DOI: 10.3109/00365528909093058
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Cancer in Patients with Crohn's Disease: A Population Study in Central Israel

Abstract: A population study of Crohn's disease (CD) during the years 1970-1980 was performed in a defined area in central Israel with 1,400,000 inhabitants. Three hundred and sixty-five patients with definite CD were identified, and a complete follow-up was obtained with particular attention to intestinal cancer. The mean follow-up time was 9.95 years (range, 1-49 years). Forty-four per cent of the patients were operated on, but only a few had total colectomy or bypass operations. Only one patient developed colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 8 publications
1
43
1
2
Order By: Relevance
“…Those who were less than 30 years old at the time of diagnosis of CD had a higher relative risk than those diagnosed at an older age. In pa tients with any colonic involvement, diagno sis at an early age entailed a comparative risk of 20.9, compared with 2.2 in those diagnosed after age 30 [8], Four earlier population-based studies found no association between CD and colo rectal cancer [20][21][22][23], However, all four failed to correct their data for the small subsets of their populations that were actually at risk, namely those with extensive, long-standing, unresected colonic disease.…”
Section: Risk In CDmentioning
confidence: 77%
“…Those who were less than 30 years old at the time of diagnosis of CD had a higher relative risk than those diagnosed at an older age. In pa tients with any colonic involvement, diagno sis at an early age entailed a comparative risk of 20.9, compared with 2.2 in those diagnosed after age 30 [8], Four earlier population-based studies found no association between CD and colo rectal cancer [20][21][22][23], However, all four failed to correct their data for the small subsets of their populations that were actually at risk, namely those with extensive, long-standing, unresected colonic disease.…”
Section: Risk In CDmentioning
confidence: 77%
“…In Crohn disease patients, the distribution of adenocarcinoma mirrors that of inflammation. Therefore, Crohn diseaserelated adenocarcinoma more frequently occurs in the Several studies have shown an increased risk for developing adenocarcinoma in the small bowel in Crohn disease patients, with a relative risk 15-50 times greater than that of the general population [2,[32][33][34]. The cumulative risk has been reported as 0.2% at 10 years, and 2.2% at 25 years after the onset of the disease [6].…”
Section: Discussionmentioning
confidence: 97%
“…The appearance of colorectal cancer in our patients with Crohn’s disease is a reality, despite the fact that Greece, due to environmental and other factors, has the lowest incidence of colorectal cancer among the European Union countries. We must bear in mind, however, that in some Mediterranean countries such as Israel [45]and countries of north Europe (Sweden) [46], the incidence of colorectal cancer among patients with Crohn’s disease is not different from that expected in the general population.…”
Section: Discussionmentioning
confidence: 99%